ASPEK MATEMATIS PADA SENI KERAJINAN GERABAH KASONGAN - Rahayu Maya Sari, Ana Easti (Widya Warta, 2020)
The purpose of this research is to find out the mathematical aspects in every field of life that are influenced   by   Kasongan   earthenware   art.   The   subjects   of   this   study   were   traditional earthenware artisans, modern earthenware artisans, and carving craftsmen. The object of this research  is  the  activity  of  earthenware  producers.  The  type  of  this  research  is  a  qualitative descriptive study and it was analyzed based on qualitative data analysis techniques. The data are in the form of interviews. The data validation of this study applied triangulation of sources. The  results  of  this  study  are  in  the  form  of  mathematical  activities  found  in  the  activities  of Kasongan  craftsmen  in  the  process  of  making  earthenware  vessels  in  general  in  Bangunjiwo Village,  Kasihan  District,  Bantul  Regency,  DIY  Province,  include  1)  land  management,  2) earthenware formation, 3) drying, 4) burning and 5) marketing. Each activity is described to see  the  mathematical  aspects  contained  therein  by  using  the  guidelines  of  six  fundamental mathematical aspects according to Alan J Bishop. Overall mathematical activities contained in each  of  these  craftsmen  activities  include  1)  Counting:  finger  and  body  counting,  accuracy, approximation,powers,  2)  Location:  environmental  location,  straight  and  curved  lines, mapping,  linkages,  circles,  ellipse,  3)  Measuring:  estimation,  length,  area,  volume,  time, temperature , weight, ordering, qualities, estimation, money, 4) Designing: design, shape, form, aesthetics,  objects  compared  to  properties  of  form,  large,  small,  similarity,  congruence, properties  of  shapes,  common  geometric  shapes,  surfaces,  symmetry,  proportion,  ratio,  scale-model enlargements, rigidity of shapes, 5) Playing: fun, modeling, imagined reality, rule-bound activity,  procedures,  chances,  prediction  plan  strategy,  and  6)  Explaining:  similarities,  story explanation, linguistic explanations, symbolic explanations.